Fetal But Not Maternal Angiotensin Converting Enzyme (ACE)-2 Gene Rs2074192 Polymorphism is Associated with Increased Risk of Being a Small For Gestational Age (SGA) Newborn - Jing He; Yong-Ping Lu; Jian Li; Tao-Yuan Li; Xin Chen; Xu-Jing Liang; Wen-Jing Chen; Sai-Nan Pi; Berthold Hocher; You-Peng Chen (Kidney & Blood Pressure Research, 2018)
Background/Aims: The maternal and fetal Renin-Angiotensin-System is involved in the control of pregnancy outcomes such as blood pressure control and gestational age. However, very little is known about the impact of the angiotensin converting enzyme 2 (ACE2) on pregnancy outcome. We thus performed a prospective clinical observational study analyzing the association of maternal and fetal ACE2 gene rs2074192 polymorphism with fetal growth during pregnancy. Methods: 898 singleton pregnant women were prospectively recruited. 739 pregnant women finally participated in the study and were genotyped. 474 women also donated umbilical cord blood for gene analysis of their offspring. All data such as basic demographic information, data from birth records, biochemical and immunological parameters, as well as Doppler ultrasonographic findings during pregnancy were collected. Fetal and maternal ACE2 gene rs2074192 polymorphism was genotyped by DNA sequencing. Results: Our analysis showed that the maternal ACE2 gene rs2074192 polymorphism was not associated with gestational hypertension, gestational diabetes mellitus, anemia, postpartum hemorrhage and fetal growth. However, neonates having rs2074192 T allele were more likely to be born as small for gestational age (SGA) babies. After multivariable logistic regression considering known confounding, we could demonstrate that the neonatal rs2074192 T allele was an independent risk factor for SGA (OR: 22.93, 95%CI: 1.26∼418.77, P< 0.05). Conclusion: This is the first study showing that the babies but not their mothers with ACE2 gene rs2074192 T allele had a high risk for SGA, which contributes to metabolic syndrome and cardiovascular diseases in later life.